Aerobic bacteriological analysis of bronchoalveolar lavage fluid in patients with pulmonary infection: a tertiary care hospital study - Akhtar, Shahida; Nazir, Asifa; Bashir, Humaira (International Journal of Research in Medical Sciences, 2021)
Background: Respiratory tract infection are an important cause of mortality and morbidity worldwide. The prevalent bacterial agents and their antimicrobial resistance patterns differs, both geographically and over time. Bronchoalveolar lavage has improved sensitivity and specificity of diagnostic techniques in diagnosis of pulmonary infections. The present study aimed to determine the current aerobic bacterial isolates and their sensitivity pattern obtained from the bronchoalveolar lavage (BAL) fluid of patients with pulmonary infection. Methods: BAL samples received from the patients of suspected respiratory tract infections over a period of one year, from June 2018 to May 2019 were processed by standard methods for isolation and identification. The antimicrobial susceptibility was done by the Kirby-Bauer disc diffusion method as per the CLSI guidelines. Results: Out of 322 BAL samples, 84 (26.08%) were found to be culture positive for bacterial isolates. Of those, 44 samples (52.38%) from among males and 40 samples (47.61%) from among females were culture positive .The predominant organism isolated was Pseudomonas aeruginosa 46 (54.76%) followed by Acinetobacter baumanii 13 (15.47%), Escherichia coli 10 (11.90%), Klebsiella pnuemoniae 6 (7.14%) Enterobacter sp 3 (3.57%), Staphylococcus aureus 3 (3.57%), Enterococcus sp 2 (2.38%) and Sphingomonas sp 1 (1.19%). The Gram-negative organisms showed maximum sensitivity to colistin (100%) while as vancomycin and linezolid were the most effective drugs against Gram positive organisms. Conclusions: Bronchoalveolar lavage has improved sensitivity and specificity in diagnosis of pulmonary infections. It is important to have an updated local antibiogram for each hospital and regular surveillance and monitoring of antibiotic resistance and the changing patterns of the bacterial pathogens is a must for better patient management.